2017
DOI: 10.1121/1.4996002
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variation in Risso's dolphin echolocation click spectra

Abstract: Discrimination of bioacoustic signals to the species or population level is critical for using passive acoustic monitoring to study cetacean ecology. Risso's dolphins off southern California have distinctive peaks and notches in their echolocation clicks, but it was unknown whether Risso's dolphins from other geographic areas have similarly distinctive click spectra and whether populations are acoustically distinct. This study investigates using clicks for species and population identification by characterizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 63 publications
0
11
1
Order By: Relevance
“…Because the sampling rate used in this study (50 kHz) did not allow us to record the full spectrum of echolocation clicks, we did not attempt to separate signals into probable species and pooled all acoustic data under a single delphinid group. Nevertheless, of the five dolphin species that occur in our study area 20 , Risso's dolphin clicks have peaks frequencies slightly higher than frequencies recorded by our system 61 . Moreover, in the Azores, Risso's dolphins show a preference for habitats close to the islands 16 and striped dolphins are only occasional visitors 20 .…”
Section: Discussioncontrasting
confidence: 55%
“…Because the sampling rate used in this study (50 kHz) did not allow us to record the full spectrum of echolocation clicks, we did not attempt to separate signals into probable species and pooled all acoustic data under a single delphinid group. Nevertheless, of the five dolphin species that occur in our study area 20 , Risso's dolphin clicks have peaks frequencies slightly higher than frequencies recorded by our system 61 . Moreover, in the Azores, Risso's dolphins show a preference for habitats close to the islands 16 and striped dolphins are only occasional visitors 20 .…”
Section: Discussioncontrasting
confidence: 55%
“…, Soldevilla et al . ), thus highlighting the complex relationship between click structure and sound production morphology.…”
Section: Available Datamentioning
confidence: 97%
“…) but not all delphinid species (Soldevilla et al . ). Species producing this click subtype tend to have two slightly or moderately asymmetric bursae complexes, and their posterior melon has lateral branches that extend through unique pyramidal lipid basins to connect with both bursae complexes (Cranford et al .…”
Section: Available Datamentioning
confidence: 97%
“…Previous research have also demonstrated that coefficients in cepstral analysis (inverse Fourier transform of the logarithm of the estimated spectrum of a signal) had good classification performance for some species (e.g. G. griesus, M. densirostris and G. macrorhynchus), with little influence of sound propagation and variation resulting from different recording platforms [15,63]. Additionally, energy amplitude, off-axis click distortion and transmission beam-widths may contain some species-specific information.…”
Section: Plos Onementioning
confidence: 99%
“…Acoustic parameters of odontocete clicks vary depending on their sound production morphology [14], with some species having the ability to optimize their clicks within the context of the specific habitat [15]. These parameters are further influenced by sound propagation [11], off-axis effects [16] and differences in recording systems [14].…”
Section: Introductionmentioning
confidence: 99%